2022
DOI: 10.1186/s40695-022-00074-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain in midlife women: a growing problem in need of further research

Abstract: More than 10% of American adults experience some level of daily pain, and nearly 40 million (17.6%) experience episodes of severe pain annually. Women are particularly impacted by both episodic and chronic pain with higher prevalence and a greater level of pain-related disability compared to men. Midlife is a critical period for women during which the frequency of pain complaints begins to increase. Although pain is known to be influenced and controlled by sex hormones, it has not been widely recognized as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We speculate that women may be more prone to chronic pain due to specific physiological and psychological gender-specific characteristics. 16,17 Pavlović et al 18 also showed differences in chronic pain predisposition between male and female patient. Female endocrine and nervous systems are more sensitive than males, and affected by various factors, which makes them more prone to chronic pain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We speculate that women may be more prone to chronic pain due to specific physiological and psychological gender-specific characteristics. 16,17 Pavlović et al 18 also showed differences in chronic pain predisposition between male and female patient. Female endocrine and nervous systems are more sensitive than males, and affected by various factors, which makes them more prone to chronic pain.…”
Section: Discussionmentioning
confidence: 95%
“…Female endocrine and nervous systems are more sensitive than males, and affected by various factors, which makes them more prone to chronic pain. 18 , 19 In addition, hormonal changes during childbirth and menopause can affect pain sensitivity. 20 Moreover, psychological and socioeconomic factors may also influence predisposition to chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…One might assume more sensitive skin sensation in women because of lower skin thickness, softertexture of the skin and more superficial vascularization and innervation. In general, studies report a lower pain level in women [ 31 , 32 ]. An additional finding could be documented comparing shaved or not shaved skin area in men [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews of opioids have studied opioid use disorders and opioid misuse in primary care settings [39][40][41]. For example, younger age groups or female groups in primary care settings are often under-studied with poorly reported prevalence and risk factors [42][43][44][45]. To our best knowledge, a review of opioid prescriptions for chronic non-cancer pain patients in primary care providers based on large routinely collected electronic health records, claims, and observational datasets, which we term "big data", remains lacking.…”
Section: Introductionmentioning
confidence: 99%